Perancangan Sistem Monitoring Penjualan Untuk Optimalisasi Penjualan Sayuran Pada Kelompok Tani Hidroponik Menggunakan Metode Single Exponential Smoothing (SES) - Novi Indrayani; Nasruddin Bin Idris (Jurnal Ilmiah Matrik, 2020)
One important aspect of buying and selling activities is the proper tabulation of sales data. During its development, many ways are used to store and process sales data, systems with varied features and different results according to user needs. In this study, researchers developed a system that can be accessed easily, web-based with a case study of selling hydroponic vegetables. This Sales Monitoring System can be used as a tool to record sales data, so that farmers are expected to use the data to predict the types of vegetables that should be planted. The forecasting process uses the Single Exponential Smoothing method using sales data as reference data. This system can also use to monitor the vegetables that are put into stalls or market places, and also see the accumulated monthly income. Apart from farmers, there are 3 other user categories in this system; admin, accountant and super admin